2001
DOI: 10.1148/radiol.2213010358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Posttreatment Response of Hepatocellular Carcinoma with Contrast-enhanced Coded Phase-Inversion Harmonic US: Comparison with Dynamic CT

Abstract: With enhancement, coded harmonic US depicted tumor vascularity by showing tumor vessels in a real-time fashion at continuous imaging and tumor parenchymal flow at interval-delay scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 21 publications
1
93
0
4
Order By: Relevance
“…Studies have now shown that HBV genotype correlates with the risk for HCC and that genotype C carries two-to threefold higher risk than genotype B in developing HCC [10,[14][15][16][17][18][19]. Other HBV variants, such as precore, basal core, and pre-S deletion mutants, may also influence the development of HCC in carriers [15,[19][20][21][22][23][24][25].…”
Section: Hepatitis B Infectionmentioning
confidence: 99%
“…Studies have now shown that HBV genotype correlates with the risk for HCC and that genotype C carries two-to threefold higher risk than genotype B in developing HCC [10,[14][15][16][17][18][19]. Other HBV variants, such as precore, basal core, and pre-S deletion mutants, may also influence the development of HCC in carriers [15,[19][20][21][22][23][24][25].…”
Section: Hepatitis B Infectionmentioning
confidence: 99%
“…In the management of HCC, despite advances in diagnostic imaging techniques such as ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI), many difficulties remain, such as screening, staging, evaluation of treatment response, treatment guidance, identification of local recurring nodules after treatment, and diagnosis of intrahepatic recurrence after treatment. In fact, among these problems, Levovist-enhanced US has made a certain contribution to differential diagnosis [1,2,3], evaluation of malignancy grade [4], evaluation of therapeutic response to transcatheter arterial chemoembolization (TACE) [5,6,7], and needle insertion guidance [8,9]. However, there are still significant limitations in the evaluation of the therapeutic response to radiofrequency ablation (RFA) [10], screening or staging.…”
Section: Introductionmentioning
confidence: 99%
“…Among these problems, Levovist-enhanced US has made a certain contribution to differential diagnosis [5,6,7], evaluation of malignancy grade [8], evaluation of therapeutic response to transcatheter arterial chemoembolization (TACE) [9,10,11], and needle insertion guidance [12, 13]; however, there are still remarkable limitations in the evaluation of the therapeutic response to radiofrequency ablation [14], screening or staging.…”
Section: Newly Introduced Diagnostic Techniquesmentioning
confidence: 99%